Pengaruh Orientasi Pelanggan dan Kemitraan terhadap Kinerja Pemasaran dengan Mediasi Kemampuan Pemasaran pada Outlet Retail Rokok Gudang Garam di Kota Pontianak - Ari Priyanto; Indra, Ikhsan Prasetya; Fadilah, Mega Fianita; Sibuea, Budi Pratomo (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
An 11% increase in tobacco excise tax led to a decline in sales of Gudang Garam’s main products in Pontianak in 2022. This condition underscores the importance of examining the company’s marketing strategies. Retail outlets in Pontianak have established strong relationships with Gudang Garam and apply a customer-oriented approach, which is expected to enhance their marketing performance. This study aims to examine the effects of customer orientation and partnership on marketing performance, with marketing capability serving as a mediating variable, among retail outlets in Pontianak. The study population consists of all retail outlets selling Gudang Garam cigarette products in Pontianak, with a sample of 100 respondents. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The results reveal that customer orientation and partnership have positive and significant effects on marketing performance. In addition, customer orientation and partnership also positively and significantly influence marketing capability. Furthermore, marketing capability is found to mediate the effects of customer orientation and partnership on marketing performance. The strongest effect is observed in the relationship between customer orientation and marketing performance, with a coefficient value of 0,677 and a p-value of 0,000. These findings indicate that customer orientation is a key factor in driving marketing performance, supported by marketing capabilities that are adaptive, innovative, and responsive to changing market demands.